Model for Increasing the Capacity of Emergency Response Teams in Catastrophic Emergencies at the Teaching Hospital at Grandmed Hospital, Lubuk Pakam in 2023 - Lutfi Indra Jaya Sebayang (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Catastrophic emergencies are critical conditions that require hospital readiness to provide a rapid, precise, and coordinated response. Teaching hospitals, in addition to functioning as health service centers, also play a crucial role in developing human resource capacity, including in handling large-scale disasters and emergencies. This study aims to design and develop a model for enhancing the capacity of the Emergency Response Team (ERT) in dealing with catastrophic emergencies at Grandmed General Hospital. The research method used was descriptive analytical with a case study approach, involving needs identification, initial team capacity analysis, intervention strategy formulation, and evaluation of the effectiveness of training and simulation programs. The results indicate that ERT capacity enhancement can be achieved through a combination of technical training, integrated simulations, the development of structured standard operating procedures (SOPs), and strengthening cross-unit coordination. The resulting model is able to improve individual competency and teamwork in responding to emergencies, as evidenced by improved skill evaluation scores and response speed during disaster simulation tests. Therefore, this model can be used as a reference in developing a disaster management system in teaching hospitals to realize resilient, adaptive, and patient safety-oriented health services.